EVALUATION THE EFFECT OF CATALYST DEACTIVATION ON AMONIA SYNTHESIS SYSTEM OPERATIONS - Baihaqi, Muhammad
Catalyst deactivation is one of the problems encountered in industrial-scale ammonia production. Deactivation of the catalyst can be caused by increasing the catalyst service life and the interaction of toxic compounds on the surface of the catalyst. Catalyst deactivation causes a decrease in conversion in the ammonia reactor. Ammonia factory productivity can be maintained by adjusting operating conditions, such as by increasing the operating pressure and temperature in the ammonia reactor. The decrease in conversion will be followed by an increase in the molar flow of the reactor gas output. After going through the phase of separation of ammonia, the reaction product in the form of gas is sent back to the reactor by the synloop compressor as circulation gas. Thus, a decrease in catalyst activity will cause an increase synloop pressure and compressor load (energy consumption). This condition can be returned to close to initial condition when the circulation gas flow rate is reduced by increasing the exhaust gas flow (purge gas). The phenomenon of decreased catalyst activity have been evaluated by simulating the steady conditions of the process using Aspen HYSYS. The results of this study were obtained as a simulation model that was validated with the operating conditions of the ammonia plant. By using the optimizer feature on Aspen HYSYS to process data operations in the synthesis section since December 2012, the equation for the reduction in catalyst activity in the ammonia synthesis reactor is "y =1.0000-0.001x" (a decrease in activity of 0.1% per year) with a catalyst activity value in January 2020 of 81.20%. Ammonia production in that year could be maintained with a compressor shaft rotational speed of at least 13,480 rpm and a reactor inlet temperature of at least 349oC. Ammonia catalyst replacement was predicted to be carried out in December 2023 with a catalyst activity value of 76.50%. In that year the maximum speed of the compressor shaft rotates at 13.620 rpm and maintains a minimum reactor inflow temperature of 353oC.